Índice de anomalia de chuva (IAC) dos municípios do Rio Grande do Sul afetados pelas estiagens no período de 1991 a 2012 - Gross, Joceli Augusto (2015)
The present research work had as objective to analyse the relation between the municipalities of the State of Rio Grande do Sul affected by the droughts according to the emergency decrets and to the index of rain anomaly (IAC) in the period of 1991 to 2012. The motodology constituted of the analysis of pluviometric preciptation data acquired in the website HidroWeb of National Agency of Water (ANA) and in the National Institute of Meteorology (INMET) website using the Index of rain anomaly developed by Rooy (1965) and data of emergency decrets provided by the Civil Defense - RS. Data were analysed in order to identiy the municipalities affected by the droughts and its caracterization considering nagatives preciptation anomalies occurences according to IAC. Utilizating data from IAC, it was verified duration periods, itensity and droughts frequency by municipality. The emergency decrets where analysed in order to verify the total amount in the State, and on each municipality. In the end, it was realized an integrated variable analisys, to determinate the period of duration and intensity of the droughts by minicipalities issued emergency decrets in the analisys period. The results showed, that the majority of the emergency decrets analyzed were recorded after three consecutive months of droughts ranging from smooth to moderate, and the droughts acording to IAC occured mostly in the western State, mainly on summer, autun and winter. Furthermore, it was observed that the second hald of the analised period, a greater doughts month number by municipalieties, higher percentual of affected areas by negatives anomalies of preciptation, mostly negative rain anomaly rates, besides a greater number of recorded emergency decrets, that indicates a tendency a decrese on pluviometrics preciptations in the State of Rio Grande do Sul in the last decade, in the analised period.